Alteration in host metabolism in sarcoptic mite infestation in goats - MOHAPATRA, M; BASOI, P C; PARIDA, A (The Indian Journal of Animal Sciences, 2013)
Changes in blood composition of Ganjam does maintained on natural browsing with concentrate feeding and naturally infested with sarcoptc mites were studied. The mite infestation brought about a depression in serum acid phosphatase and aspartate transaminase activity. whereas serum creatinine concentration was elevated by this infestation. Serum alanme transaminase activity and total protein concentration remained unaffected by sareoptie mite infestation. A nonsignificant elevation in serum alkaline phosphatase activity and decline in serum urea and cholesterol concentration were observed.